Patient experiences with family medicine: a longitudinal study after the Dutch health care reforms in 2006 - Hombergh, Pieter van den; Wensing, Michel (BMC family practice, 2016)
In 2006 The Dutch Health Care system changed to a market oriented system. The GP remuneration changed from ± 2/3 capitation patients and 1/3 private patients before 2006 to a mixed payment scheme. From 2006 onward every patient was insured and the GP received partly capitation, partly fees for consultations and for specific services. This change coincided with many other organisational changes in General Practice care. Our research question was if during the years after 2006 patient experiences of Dutch family practice had changed. We also wanted to explore the influence of patient and practice characteristics on patient experiences. Data on patient experiences were available from 2007 to 2012.
Gesehen am 06.03.2018